The Influence of Commitment, Loyalty, and Work Environment on Employee Performance at the Election Supervisory Body of North Sumatra Province - Rafles Alexander Simanjuntak; Felicya Tiopan; Nicky Haitmen; Lenta Friska Purba; Nasib Nasib (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study examines the factors that influence employee performance at the Bawaslu of North Sumatra Province, an institution with high work pressure in maintaining election integrity. The main focus of this study is to see the extent to which commitment, loyalty, and work environment impact staff productivity. Using quantitative methods with multiple linear regression analysis, the results of the study revealed three important points Commitment & Loyalty: Employees who have a high sense of attachment and dedication are proven to work far beyond the established standards. Work Environment: Physical facilities and a supportive work atmosphere greatly help employees complete complex supervisory tasks. Simultaneous Impact: Together, these three factors contribute greatly to organizational effectiveness. To increase public trust and maintain election transparency, the North Sumatra Bawaslu (Elections Supervisory Agency) needs to strengthen its internal culture and improve work facilities. By maintaining staff commitment and comfort, the agency can remain professional and resilient in the face of challenging election oversight dynamics.